Elephants in the understory: opposing direct and indirect effects of consumption and ecosystem engineering by megaherbivores. Issue 11 (November 2016) - Coverdale, Tyler C.; Kartzinel, Tyler R.; Grabowski, Kathryn L.; Shriver, Robert K.; Hassan, Abdikadir A.; Goheen, Jacob R.; Palmer, Todd M.; Pringle, Robert M.
Abstract: Positive indirect effects of consumers on their resources can stabilize food webs by preventing overexploitation, but the coupling of trophic and non‐trophic interactions remains poorly integrated into our understanding of community dynamics. Elephants engineer African savanna ecosystems by toppling trees and breaking branches, and although their negative effects on trees are well documented, their effects on small‐statured plants remain poorly understood. Using data on 117 understory plant taxa collected over 7 yr within 36 1‐ha experimental plots in a semi‐arid Kenyan savanna, we measured the strength and direction of elephant impacts on understory vegetation. We found that elephants had neutral effects on most (83–89%) species, with a similar frequency of positive and negative responses among the remainder. Overall, estimated understory biomass was 5–14% greater in the presence of elephants across a range of rainfall levels. Whereas direct consumption likely accounts for the negative effects, positive effects are presumably indirect. We hypothesized that elephants create associational refuges for understory plants by damaging tree canopies in ways that physically inhibit feeding by other large herbivores. As predicted, understory biomass and species richness beneath elephant‐damaged trees were 55% and 21% greater, respectively, than under undamaged trees. Experimentally simulated elephant damage increased understory biomass by 37% and species richness by 49% after 1 yr. Conversely, experimentally removing elephant damaged branches decreased understory biomass by 39% and richness by 30% relative to sham‐manipulated trees. Camera‐trap surveys revealed that elephant damage reduced the frequency of herbivory by 71%, whereas we detected no significant effect of damage on temperature, light, or soil moisture. We conclude that elephants locally facilitate understory plants by creating refuges from herbivory, which countervails the direct negative effects of consumption and enhances larger‐scale biomass and diversity by promoting the persistence of rare and palatable species. Our results offer a counterpoint to concerns about the deleterious impacts of elephant "overpopulation" that should be considered in debates over wildlife management in African protected areas: understory species comprise the bulk of savanna plant biodiversity, and their responses to elephants are buffered by the interplay of opposing consumptive and non‐consumptive interactions.